Efektivitas Aplikasi Ujian Berbasis Komputer Noninternet dalam Penilaian Akhir Semester Siswa Menengah Atas - Soni, Jefri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2022)
The purpose of this study is to find out; (1) assessment techniques used in the end-of-semester assessment at SMA Negeri 1 Rantau Selamat before using a computer-based examination application; (2) how to implement a non-internet computer-based examination application at SMA Negeri 1 Rantau Selamat, and; (3) the effectiveness of non-internet computer-based exam applications as a means of in the end-of-semester assessment at SMA Negeri 1 Rantau Selamat. The research method used is a qualitative descriptive method. Data were collected by the method of interviews, observations and study of documents. The sampling technique used in this study was purposive sampling. The results showed that (1) the assessment technique that is often used in end-of-semester assessments is to use test papers and also use online exams based on internet by utilizing Google LMS and Microsoft LMS; (2) The implementation of non-internet computer-based exams is carried out with the planning stages of the IT team, question preparation workshops by teachers, and scheduled implementation of exams; (3) the application of non-internet computer-based examinations has an impact on the efficiency of the results examination time, the objectivity of the assessment, and the optimization of the academic honesty of students.